Update of the list of qualified presumption of safety (QPS) recommended microbiological agents intentionally added to food or feed as notified to EFSA 21: Suitability of taxonomic units notified to EFSA until September 2024 - EFSA Panel on Biological Hazards (BIOHAZ); Ana Allende; Avelino Alvarez‐Ordóñez; Valeria Bortolaia; Sara Bover‐Cid; Alessandra De Cesare; Wietske Dohmen; Laurent Guillier; Liesbeth Jacxsens; Maarten Nauta; Lapo Mughini‐Gras; Jakob Ottoson; et al. (EFSA Journal)
Abstract The qualified presumption of safety (QPS) process was developed to provide a safety assessment approach for microorganisms intended for use in food or feed chains. In the period covered by this Statement, no new information was found that would change the status of previously recommended QPS taxonomic units (TUs). The TUs in the QPS list were updated based on a verification, against their respective authoritative databases, of the correctness of the names and completeness of synonyms. Of 54 microorganisms notified to EFSA between April and September 2024 (33 as feed additives, 17 as food enzymes or additives, 4 as novel foods), 50 were not evaluated because: 12 were filamentous fungi, 1 was Enterococcus faecium and 8 were Escherichia coli (all excluded from the QPS evaluation), and 29 were TUs that already have a QPS status. One notification (Ensifer adhaerens) was already evaluated in a previous Panel Statement. Another notification (Enterococcus lactis) was already evaluated in the previous 3‐year QPS cycle and was reassessed within this document. Two TUs were notified for the first time and were assessed for a possible QPS status: Serratia plymuthica and Lacticaseibacillus huelsenbergensis. Bacillus thuringiensis and Bacillus nakamurai have been assessed for a possible QPS status in response to internal requests. The following was concluded on the five assessed TUs. L. huelsenbergensis can be granted the QPS status based on its close relatedness to several other QPS Lacticaseibacillus species. E. lactis is not recommended for the QPS status due to insufficient information on safety. S. plymuthica and B. thuringiensis are not recommended for the QPS status due to safety concerns. B. nakamurai cannot be recommended for the QPS list due to a lack of body of knowledge for its use in the food and feed chain.